PENINGKATAN HASIL BELAJAR PESERTA DIDIK KELAS IV MATERI PECAHAN MENGGUNAKAN MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA BERBASIS DIGITAL DI UPTD SD INPRES PERUMNAS 1 KOTA KUPANG - Eni Sarlina Uas; Damianus Dao Samo; Vera Rosalina Bulu (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Thesis by Eni Sarlina Uas, Student Identification Number 2101140060. The background of this research is based on the low learning outcomes of students in mathematics, particularly in the topic of fractions. This issue stems from the lack of student engagement and the use of less engaging learning media. The aim of this study is to improve the learning outcomes of grade IV students on fraction material through the implementation of the Problem Based Learning model supported by digital based media at UPTD SD Inpres Perumnas 1 Kupang City. The research method used is Classroom Action Research, which was carried out in two cycles. Each cycle consisted of the stages of planning, implementing actions, observation, and reflection. The subjects of this research were 16 students of Grade IV-A. Data collection instruments included learning outcome tests and observation sheets for teacher and student activities. Data analysis techniques were conducted using descriptive quantitative analysis. The results showed that the implementation of the Problem Based Learning model assisted by digital media can improve student learning outcomes. In cycle I, the average student score was 58.75 with a classical completeness percentage of 18.75%. After improvements were made in cycle II, the average score increased to 96.25 with a completeness percentage reaching 100%. Thus, learning using the Problem Based Learning model assisted by digital media proved to be effective in improving mathematics learning outcomes, especially in fraction material.